The Spectator, 2001-12-06 - Spectator, Valdosta State University (Valdosta State University, 2001)
The Spectator (draft copy). December 6, 2001. Vol.69 No.12. Baily responds to Living Wage -- Living Wage Campaign Timeline -- Next president expected by Jan. 1 -- Departments looking to ease growing pains.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete, rendered incorrectly, or different from final print editions. Some fonts have been changed. Processed by Dallas Suttles at Valdosta State University Archives and Special Collections, 2016. dasuttles@valdosta.edu. UUID: C89675BB-7126-432E-B2DF-9D8A502F001E PUID: fmt/354 pdf/a Page Count: 10
Keywords: Valdosta State University -- Periodicals